International business cycles: Quantifying the effects of a world market for oil - Johan Gars; Conny Olovsson (Sveriges Riksbank, 2017)
To what extent is the international business cycle affected by the fact that an essential input (oil) is traded on the world market? We quantify the contribution of oil by setting up a model with separate shocks to efficiencies of capital/labor and oil, as well as global shocks to the oil supply. We find that the shocks to the supply and the efficiency of oil both contribute to positive comovements. These two shocks are also relatively transitory, which induces high responses in output and low responses in consumption. As a consequence, the model resolves both the consumption correlation puzzle and the international comovement puzzle.
Keywords: E32; F32; F41; Q43; 330; International comovements; business cycles; oil; productivity